Reliability of DXA for the measurement of total and regional body composition in elite soccer players - Fanchini, M.; Rillo, G.; Bruno, M.; Sharp, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Dual-energy X-ray absorptiometry (DXA) is widely used for the assessment of total and regional body composition. Acquisition of the data can be done automatically with the in-built software however the software may under/overestimate regional parameters (i.e. legs). As such, the data may also be acquired by operator manual adjustment of the regions-of-interest (ROI) but the experience of the operator may influence the accuracy and reliability. In elite football monitoring leg muscle mass is relevant therefore operator adjustment may be required. The aim of this study was to examine the reliability of total and regional body composition when comparing automatic and manual ROI assessment performed by operators with different experience levels.